Metode Pratikum Sebagai Upaya Meningkatkan Motivasi Belajar Peserta Didik Pada Kegiatan Pembelajaran Daring - Arif Kristanta (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2021)
The problem to be solved in this research is how to increase the learning motivation of students who are decreasing in online learning in Sciences subjects. This study aims to describe the implementation of online learning using the practical method and to find out the extent to which this method can increase students' learning motivation. The research method used classroom action research type experiment with the Kemmis-Taggart model in two cycles. Practicum in online learning is carried out at the home of each student using tools and materials at home and in the surrounding environment without leaving the learning objectives in basic competencies. Practical guides, student worksheets, and student responses to learning methods were made using Google Form. Activities and work results in the form of answers to conceptual questions and photos or videos of experimental activities are monitored with a Google Spreadsheet linked to the Google Form. Online learning with the practicum method has been able to increase the learning motivation of students with an indicator of an increase in the number of students who take part in the online learning from 30% to 50%, and an increase in mastery of the concept of subject matter with an increase in the average value of learning outcomes from 37.2 to 74.38 in cycle I and 80.67 in cycle II.